Exploring Public Leadership Transformation for Public Service in the Digital Age: A Brief Appraisal - Mulyani, Sri (Universitas Sultan Ageng Tirtayasa, 2024)
This study explores the transformation of public leadership in public services in the digital era, with the aim of identifying the roles, challenges and opportunities that arise from technological developments. The digital era influences various aspects of public leadership, especially in terms of transparency, efficiency, and community engagement. This leadership transformation includes technology adaptation, data-driven policy implementation, and digital skills development in public leaders. With a descriptive-qualitative approacThis study explores the transformation of public leadership in public services in the digital era, with the aim of identifying the roles, challenges and opportunities that arise from technological developments. The digital era influences various aspects of public leadership, especially in terms of transparency, efficiency, and community engagement. This leadership transformation includes technology adaptation, data-driven policy implementation, and digital skills development in public leaders. With a descriptive-qualitative approach. The results of the study show that the transformation of public leadership in service in the digital era has brought significant changes in the accessibility and efficiency of public services. Government agencies now provide online services, such as document processing and tax payments, which make it easier for the public without having to visit the office. The use of social media and mobile applications also increases interaction between the government and the public. Leaders in the public sector need to adopt effective digital leadership by leveraging technology and having in-depth knowledge, communication skills, and adapting to change. Digital leadership plays a vital role in accelerating the transformation of public services by creating a collaborative and responsive work environment, as well as encouraging innovation and transparency. In doing so, digital leaders can improve the quality of public services and strengthen public trust in the face of rapid demands for change.h. The results of the study show that the transformation of public leadership in service in the digital era has brought significant changes in the accessibility and efficiency of public services. Government agencies now provide online services, such as document processing and tax payments, which make it easier for the public without having to visit the office. The use of social media and mobile applications also increases interaction between the government and the public. Leaders in the public sector need to adopt effective digital leadership by leveraging technology and having in-depth knowledge, communication skills, and adapting to change. Digital leadership plays a vital role in accelerating the transformation of public services by creating a collaborative and responsive work environment, as well as encouraging innovation and transparency. In doing so, digital leaders can improve the quality of public services and strengthen public trust in the face of rapid demands for change.